Efektivitas Metode Penanaman dan Asal Bibit Terhadap Pertumbuhan Bruguiera sexangula pada Sistem Silvofishery - Lensari, Delfy; Rahmad, Beni; Mahena, Helen Sapni; Harefa, Ribka (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study was conducted to compare the effectiveness of two planting locations (pond and riverside zone) and two seedling sources (propagule and naturally sourced seedlings) on the growth of the mangrove species Bruguiera sexangula, which is not endemic to the study site. The research employed a quantitative experimental method. The results of this study show that the source of propagule-derived seedlings has a very significant effect on plant growth. Statistically, propagule-derived seedlings produced significantly better growth in all parameters (height, diameter, number of leaves, and root length) compared to naturally sourced seedlings. Meanwhile, the factors of planting location (pond and riverside zone) and treatment combination did not show statistically significant differences. Although descriptively the riverside zone location gave better results in some parameters, the differences were not strong enough to prove that certain locations or treatment combinations were superior to others. The conclusion of this study confirms that in mangrove rehabilitation efforts in non-endemic areas, the selection of seedling propagule sources is an important factor in achieving successful growth.